Experience with genomic sequencing in pediatric patients with congenital cardiac defects in a large community hospital. Issue 2 (25th January 2018) - Hauser, Natalie S.; Solomon, Benjamin D.; Vilboux, Thierry; Khromykh, Alina; Baveja, Rajiv; Bodian, Dale L.
Abstract: Background: Congenital cardiac defects, whether isolated or as part of a larger syndrome, are the most common type of human birth defect occurring on average in about 1% of live births depending on the malformation. As there is an expanding understanding of the underlying molecular mechanisms by which a cardiac defect may occur, there is a need to assess the current rates of diagnosis of cardiac defects by molecular sequencing in a clinical setting. Methods and Results: In this report, we evaluated 34 neonatal and pediatric patients born with a cardiac defect and their parents using exomized preexisting whole genome sequencing (WGS) data to model clinically available exon‐based tests. Overall, we identified candidate variants in previously reported cardiac‐related genes in 35% (12/34) of the probands. These include clearly pathogenic variants in two of 34 patients (6%) and variants of uncertain significance in relevant genes in 10 patients (26%), of these latter 10, 2 segregated with clinically apparent findings in the family trios. Conclusions: These findings suggest that with current knowledge of the proteins underlying CHD, genomic sequencing can identify the underlying genetic etiology in certain patients; however, this technology currently does not have a high enough yield to be of routine clinical use in the screening of pediatric congenital cardiac defects. Abstract : Our experience with whole genome sequencing in patients with congenital cardiac defects suggest that genomic sequencing can identify the underlying genetic etiology in certain patients; however, this technology currently does not have a high enough yield to be of routine use in the screening of pediatric congenital cardiac defects.